MILLIMETER AND SUB-MILLIMETER-WAVE SPECTRUM OF SELENIUM DIOXIDE, SeO₂ - E. A. Alekseev; O. I. Baskakov; S. P. Dyubko (Radio Physics and Radio Astronomy, 2025)
Subject and Purpose. The work is aimed at investigating the spectra of the ground-state and a few of the excited vibrational states for the main isotopologues of the selenium dioxide molecule, SeO₂, in order to provide a reliable basis for its further search in the interstellar medium.